ARF induction in response to DNA strand breaks is regulated by PARP1 - Orlando, G; Khoronenkova, S; Dianova, I; Parsons, J; Dianov, G (Oxford University Press, 2013)
The ARF tumour suppressor protein, the gene of which is frequently mutated in many human cancers, plays an important role in the cellular stress response by orchestrating up-regulation of p53 protein and consequently promoting cell-cycle delay. Although p53 protein function has been clearly linked to the cellular DNA damage response, the role of ARF protein in this process is unclear. Here, we report that arf gene transcription is induced by DNA strand breaks (SBs) and that ARF protein accumulates in response to persistent DNA damage. We discovered that poly(ADP-ribose) synthesis catalysed by PARP1 at the sites of unrepaired SBs activates ARF transcription through a protein signalling cascade, including the NAD+-dependent deacetylase SIRT1 and the transcription factor E2F1. Our data suggest that poly(ADP-ribose) synthesis at the sites of SBs initiates DNA damage signal transduction by reducing the cellular concentration of NAD+, thus down-regulating SIRT1 activity and consequently activating E2F1-dependent ARF transcription. Our findings suggest a vital role for ARF in DNA damage signalling, and furthermore explain the critical requirement for ARF inactivation in cancer cells, which are frequently deficient in DNA repair and accumulate DNA damage.